Pengembangan Media Pembelajaran Nopobegama Pada Siswa Kelas IV Sekolah Dasar - Deviana Putri Ari Sandy (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
The teaching and learning process is an activity that must be supported from all aspects. It is not only about the teaching methods that are taken into account, but also about the learning media used. Learning media plays an important role in the teaching and learning process to enhance the effectiveness and efficiency of the ongoing learning. With the use of learning media, students can understand material from abstract to concrete, increase their interest in learning, and help make the teaching and learning atmosphere enjoyable. Observations show that the researcher will develop Nopobegama media due to the limitations of existing learning media in schools, especially at the fourth-grade level of elementary schools. The research method used is Research and Development (R&D). The techniques involve questionnaires, interviews, and documentation sheets. This study employs both qualitative and quantitative research. The result is the development of the nopobugama media with the material of cultural diversity in 4th grade based on games. The results of the feasibility test on the material were 75%, media expert 95%, small group trial 91%, and large group trial 98%. Therefore, the use of this learning media is declared very feasible to be applied in the learning process.